A theoretical framework for spending review policies at a time of widespread recession - Catalano, Giuseppe (OECD Publishing, 2018)
The aim of this paper is to propose a first theoretical framework for medium term spending reviews that determines the main factors affecting the use of these spending reviews and their impact, at a time of widespread recession. As result, it identifies four dimensions (political, social, organisational and operational) and one dynamic element (time) that influence the performance of spending reviews and should be considered in approaching this tool. Finally this paper introduces some theoretical and policy considerations, concerning both how to effectively address the five elements that influence the spending review and how a government should design this tool. JEL codes: H50, H61, H83 Keywords: Spending reviews, recession, performance budgeting, cutback management